Study of permanent residential management in Tondo Village, Palu City - Salenda, H; Malik, S M; Julia, F; Munawir, Munawir (Applied Engineering and Technology, 2022)
Currently the regional government of Central Sulawesi Province through the Ministry of PUPR has built several permanent residential units (Huntap) for victims of the natural disaster on September 28 2018 that occurred in Palu City, one of which is located in Tondo Village, right behind the Tadulako University Campus. However, based on the results of the initial survey that had been carried out, there were still some things that were not given much attention, such as the provision of housing facilities and infrastructure as well as the shape of houses and their locations that did not respond to the topographic climatic conditions in Palu City. Based on the above premise, regarding the importance of permanent housing arrangement for victims of natural disasters, a problem can be formulated, namely "What is the concept of permanent housing arrangement in Tondo Village with a healthy shelter-based approach?"This study uses a rationalistic approach. The rationalistic approach is an approach that sees truth not solely from empirical conditions but also from argumentation as a part of thinking construction. To collect information and obtain data that is directly related to the research, a direct observation was carried out which included observation at the permanent residential location of Tondo Village which was the object of this study.The design concept carried out in the arrangement of permanent housing in Tondo Village is to formulate the concept of providing housing facilities and infrastructure. In addition to this, the model of residential buildings is also designed to be more attractive, so that it will be different from the appearance of permanent residential buildings that currently exist. The house design is maximized to be able to respond to the climate around a permanent residence, so as to be able to produce designs that guarantee the health of the residents of the house. The structural system used is no different from existing huntap building structural system, namely the simple healthy instant house structure system (RISHA).